"Depicting Heavenly Reality": Non-Textual Objects as Inscriptions of Belief. (2nd October 2022) - Varela Rios, Héctor M.
Abstract: That religious objects document religion is usually construed as fact. In this paper, I also confirm that fact via five "object stories" of believers, that is, the complex and diverse lived religion displayed through my informants' (and my own) relationship with religious objects garnered through open-ended interviews and personal reflection, and also via material culture analysis using Jules David Prown. But what is *it* that religious objects document? Since the key word is document, I begin with Maurizio Ferraris' "documentality" and its constitutive rule "Object = Inscribed Act." I also realized during the interview process that my informants were describing and explaining beliefs in varying ways. To elucidate, I turn to David Morgan's typology of belief. Construing belief as a social act, I formulate the "Ferraris-Morgan" constitutive rule of religious documentality: Religious Object = Inscribed Belief. My informants' witness suggest that these objects are documents of belief: belief rediscovered, belief nurtured, belief distributed, belief used, belief identified—belief "depicted, " as one informant said. Yet, how authentic are these documentalities of belief? I use Orlando O. Espín to authenticate the "sensus fidei" depicted in these religious documents. Espín will also be helpful to ascertain what is at stake: the subversiveness they present to "official" Catholicism in general yet the preeminence they represent to everyday flourishing of believers.